SHOPEE AS THE MARKETPLACE FOR INDOMIE IN THE GLOBALIZATION ERA - Febriana Sakina; Irma Rahmayani Marpaung; M Iqbal Sitompul; Mutia Sari Dewi; Suhairi Suhairi (Indonesian Journal of Multidisciplinary Science, 2022)
One way of marketing online for your business that can guarantee increasing sales is to sell in the marketplace. This research aims to find out the use of Shopee as a marketing medium for Indomie products in the global era. This research model is a qualitative approach model. Data collection techniques use document studies where document studies are carried out by reviewing documents related to research topics. This subject and research is Indomie Products. The result of this research is the use of Shopee as an indomie marketing medium so that indomie marketing can cover a wider market and be able to compete with other products, Shopee provides free shipping and flash sale programs, can be sent throughout the region, and makes it easier for customers to shop and choose various flavors from Indomie.